1975
DOI: 10.1080/00332747.1975.11023846
|View full text |Cite
|
Sign up to set email alerts
|

Ego Modalities in the Manifest Dreams of Male and Female Chicanos

Abstract: When the manifest dreams of young adult male and female Chicanos were examined through an inventory which captures the dream content and pattern, striking differences between male and female dreams were found in the areas of setting, characters, interaction, self, instinctual modalities, and realism. Generally speaking, the men's internal psychic world, as viewed through their dreams, tended to be organized around a highly visible and demarcated self seen as robustly active, randomly in motion, and often cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Further, female dreamers typically report more friendly interactions among dream characters, with less aggression and sexual activity than reported by male dreamers (Domhoff, 1996;Hall & Van de Castle, 1966;Hall et al, 1982;Krippner & Weinhold, 2002). This finding was also shown by Brenneis and Roll (1975) using different content scales. Also, while females typically report equal percentages of male and female characters involved in both aggressive and friendly interactions, male dreamers more often report aggression with other male characters and more friendly interactions with female characters (Domhoff, 1996;Garfield, 1988).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Further, female dreamers typically report more friendly interactions among dream characters, with less aggression and sexual activity than reported by male dreamers (Domhoff, 1996;Hall & Van de Castle, 1966;Hall et al, 1982;Krippner & Weinhold, 2002). This finding was also shown by Brenneis and Roll (1975) using different content scales. Also, while females typically report equal percentages of male and female characters involved in both aggressive and friendly interactions, male dreamers more often report aggression with other male characters and more friendly interactions with female characters (Domhoff, 1996;Garfield, 1988).…”
Section: Introductionmentioning
confidence: 86%
“…Male dreamers also report a greater frequency of violent and aggressive interactions, sexual activity, and achievement strivings compared to female dreamers (Hall et al, 1982;Van de Castle, 1971;Winget et al, 1972). In dreams with aggressive content, male dreamers also typically report a higher percentage of physical aggression than reported by females (Brenneis & Roll, 1975;Domhoff & Schneider, 1999).…”
Section: Introductionmentioning
confidence: 96%
“…Although there are no studies using the Hall/Van de Castle system that included Mexican-American male students, Brenneis (1976) and Brenneis and Roll (1975) compared the dream reports of Mexican-American and Anglo-American male and female students at the University of New Mexico using the scale of "34 ego dimensions" developed by Brenneis and discussed in Chapter 2. Their results are not strictly comparable with other findings in this chapter, but there is enough overlap in some of the scales to make several of their findings of interest.…”
Section: Mexican-americans At Two Different Universitiesmentioning
confidence: 99%
“…Research projects which have attempted to take into account the rich complexity of the Chicano experience include the work of Brenneis & Roll (1975) which relied on the use of Spanish in the home to identify adherence to cultural norms and Edgerton & Karno (1971) which investigated differences between Chicanos who speak mainly Spanish and those who do not speak Spanish. Their findings indicated that "the more commonly described cultural traits of Mexican-American-e.g., fatalism, familism, strong attachment to formal religious values, patriarchal authoritarianism, and conservative morality regarding deviant behavior -are applicable (and even here with many exceptions and qualifications) only to those persons who speak mainly or only Spanish" (1971, p. 290).…”
Section: / Errors In Diagnosismentioning
confidence: 99%